Nasal Immunization Confers High Avidity Neutralizing Antibody Response and Immunity to Primary and Recurrent Genital Herpes in Guinea Pigs - Persson, Josefine; Zhang, Yuan; Olafsdottir, Thorunn A.; Thörn, Karolina; Cairns, Tina M.; Wegmann, Frank; Sattentau, Quentin J.; Eisenberg, Roselyn J.; Cohen, Gary H.; Harandi, Ali M. (Frontiers in Immunology, 2016)
Genital herpes is one of the most prevalent sexually transmitted infections in both the developing and developed world. Following infection, individuals experience life-long latency associated with sporadic ulcerative outbreaks. Despite many efforts no vaccine has yet been licensed for human use. Herein, we demonstrated that nasal immunization with an adjuvanted HSV-2 gD envelope protein mounts significant protection to primary infection as well as the establishment of latency and recurrent genital herpes in guinea pigs. Nasal immunization was shown to elicit specific T cell proliferative and IFN-γ responses as well as systemic and vaginal gD-specific IgG antibody (Ab) responses. Further, systemic IgG Abs displayed potent HSV-2 neutralizing properties and high avidity. By employing a competitive surface plasmon resonance analysis combined with a battery of known gD-specific neutralizing monoclonal Abs (MAbs), we showed that nasal immunization generated IgG Abs directed to two major discontinuous neutralizing epitopes of gD. These results highlight the potential of nasal immunization with an adjuvanted HSV-2 envelope protein for induction of protective immunity to primary and recurrent genital herpes.